การบำบัดน้ำเสียสีย้อมประเภทละลายน้ำด้วยเกล็ดไคโตซานจากเปลือกกุ้ง - เบญจวรรณ สุทธไชย (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The chitosan flakes prepared from shrimp shells were used to remove water soluble dyes in wastewater. The deacetylation and average molecular weight were 90.1±4.5 % and 1.8X10⁵ Dalton, respectively. Effluents from dyeing bath (acid dye, direct dye and reactive dye) and total wastewater from 3 case factories were studied. The chitosan flakes were ground to 710-850 µm. In case of effluent from dyeing bath, the optimum condition was obtained by adjusting the pH to be 6, dosing of 0.4 g chitosan per 200 ml effluent at 150 rpm for 4 hours. It was found that the removal efficiencies in absorption at maximum wavelength and in peak area of visible region of acid dye were 90.24±0.36 % and 89.06±0.36 %, respectively. Those of direct dye were 98.87±0.23 and 89.53±0.66, respectively. However, chitosan could not remove reactive dye. The optimum condition of wastewater from Asia Fiber Public Co., Ltd. was similar to dyeing effluent. But the optimum pH for total wastewater from Sinsaenee Co., Ltd and Thanapaisal R.o.p were at 5. Chitosan doses were 0.2 g for Sinsaenee Co., Ltd and 0.4 g per 200 ml wastewater for Thanapaisal R.O.P at 80 rpm and 4 hours. The removal efficiencies in absorption at maximum wavelength of total wastewater from these 3 case factories were 87.89±0.45, 84.72±0.60 and 90.39±0.82, respectively and those in peak area at visible region were 83.69±0.48, 77.16±0.92 and 85.20±1.21, respectively. The adsorption rate in synthetic dye wastewater was higher than in real wastewater, expecting that anionic ion in auxiliaries competed the electrostatic attraction between anionic sulphonate groups (SO⁻₃) of dyes and the cationic amino group (NH⁺₃) of chitosan. The adsorption isotherms of synthetic acid and direct dye solution could be fitted well with both Langmuir and Freundlich equations. The maximum sorption capacities of chitosan for acid and direct dyes by Langmuir equation were 13.40 and 25.51 mg/g, respectively. Klebsiella oxytoca, Alcaligenes faecalis and Comamonas acidovoran were found in chitosan sludge incubated at 37℃.